Descriptive Study of Cognitive Development of Children Aged 5-6 Years in Preschool Education at Pambudi Bhakti Turirejo Kindergarten Demak - Desi Soraya; Kalimatus Sa’diyah; Mudy Oktiningrum (Napande: Jurnal Bidan, 2026)
Background: Cognitive development is a crucial component of early childhood education, as it significantly influences children’s ability to think, reason, and solve problems in daily life. However, cognitive development among children aged 5–6 years in preschool settings has not yet reached optimal levels across several developmental indicators. Method: This study employed a quantitative descriptive design and was conducted at Pambudi Bhakti Turirejo Kindergarten, Demak. The participants included 61 children aged 5–6 years, selected using a total sampling technique. Data were collected through direct observation using the Pre-Screening Development Questionnaire (KPSP) and analyzed descriptively using frequencies and percentages. Ethical approval was obtained under EC number 052/KEPK/UNPRI/II/2025. Result: Most participants were aged 6 years (72.1%). The findings revealed that 60.7% of children were categorized as having doubtful cognitive development, 24.6% demonstrated appropriate cognitive development, and 14.8% were classified as deviant. Conclusion: The results indicate that the majority of children require more optimal cognitive stimulation. Therefore, the implementation of creative and child-centered learning strategies, including play-based learning, effective teacher–child interaction, and a supportive learning environment, is essential to enhance children’s cognitive development in preschool education.